Synthesis and antimicrobial activity of 4-(5-ARYL-2-FUROYL)morpholines and 4-[(5-ARYL-2-FURYL)carbonothioyl] morpholines - Yuliia Matiichuk; Yuri Gorak; Roman Martyak; Taras Chaban; Volodymyr Ogurtsov; Igor Chaban; Vasyl Matiychuk (Pensoft Publishers, 2021)
By the reaction of furan-2-carboxylic acids and furfural with diazonium salts 1a-j the arylfuran-2-carboxylic acids 4a-e and 5-arylfuran-2-carbaldehydes 5a-f were synthesized. Acids 4a-e were transformed into appropriated acylchlorides 6a-e and were used for preparation of 4-(5-aryl-2-furoyl)morpholines 7a-e. 4-[(5-Aryl-2-furyl)carbonothioyl]morpholines 8a-f were prepared from aldehydes 5a-f by using Willgerodt-Kindler reaction. The structures of the obtained compounds were confirmed by 1H NMR spectroscopy and elemental analysis. All these new compounds gave spectroscopic data in accordance with the proposed structures. The antimicrobial activities of synthesized compounds 7a-e and 8a-f were investigated and the compounds with high activity against C. neoformans ATCC 208821 were identified.